Analysis of Student Conception of Atomic Structure at the State SMA in Palu - Gavrila Gavrila; Suherman Suherman (Jurnal Akademika Kimia, 2020)
This study aimed to analyze student’s knowledge (percent) for who know concept (KC), misconception (MC), and do not know concept (DKC) on the subject of atomic structure at the state SMA in Palu. The sample of this study were students of SMAN Model Terpadu Madani, SMAN 3, and SMAN 9. Data were obtained through tracer tests of students’ conception in the form of multiple-choice consisted of 20 items accompanied by CRI (Certainty of Response Index) which was given to students to determine students' conceptions. Results of the study showed that the percentage of KC, MC, and DKC at SMAN Madani Model Palu were 65.6, 11.3, and 23.2% respectively, while at SMAN 3 Palu were 46.0, 15.1, and 38.9% respectively, and at SMAN 9 Palu were 5.9, 72.6, and 21.5% respectively.